(untitled) (Research, Society and Development, 2024)
The objective was to register the population fluctuation, in different months of the year, and the preference of the bronzed bug and the shell psyllid by clones and quadrants of the Eucalyptus crown. The research was carried out in commercial clones of Eucalyptus hybrids in Alvorada do Gurguéia-PI, Brazil. Insects were collected in the middle third of the crown. Before cutting, the branches were protected with a handle, removed with the aid of pruning, temporarily packed in plastic bags, for further identification and counting of the insects. The population fluctuation was elaborated by pest species for all clones evaluated. They were correlated with the climatic variables: T (° C), RH (%) and precipitation (mm) using Pearson’s linear correlation test. The S-N-K test was used to compare the effect of the quadrant on plague abundance. For the species Glycaspis brimblecombei, the highest incidence occurred in May to August; the eastern position of the crown is the most representative sampling point for adults and nymphs; the most attractive clone comes from the crossing of Eucalyptus tereticornis x Eucalyptus urophylla and the least attractive are hybrids from Eucalyptus grandis x Eucalyptus camaldulensis and Eucalyptus grandis x Eucalyptus urophylla. For the species Thaumastocoris peregrinus, the highest incidence was in January; The cardinal position of the collected branch did not influence the abundance of individuals collected; the most attractive clone comes from the cross between Eucalyptus grandis x Eucalyptus camaldulensis, and the least attractive comes from the cross between Eucalyptus grandis x Eucalyptus urophylla.